2020
DOI: 10.1108/ijoa-07-2019-1843
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and validating resource recombination in context of higher educational institution competitiveness

Abstract: Purpose The purpose of this paper is to explore how resource recombination (RR) may be conceptualized with special reference to the competitiveness of Higher Education Institutions (HEI). Design/methodology/approach The paper consists of two main studies. Building on pertinent available literature on the subject area, a qualitative investigation was conducted with the help of a semi-structured interview guide. Findings of study one were systematically analysed against a literature derived template. Study two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 40 publications
1
9
0
21
Order By: Relevance
“…Accordingly, our findings are consistent with the recommendations of previous studies (e.g. Muneeb et al, 2020;Deya, 2016), which emphasize that the deployment of DC under wrong casual assumptions may have a negative impact on an HEI's competitiveness.…”
Section: Findings and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accordingly, our findings are consistent with the recommendations of previous studies (e.g. Muneeb et al, 2020;Deya, 2016), which emphasize that the deployment of DC under wrong casual assumptions may have a negative impact on an HEI's competitiveness.…”
Section: Findings and Discussionsupporting
confidence: 93%
“…Competitive advantage rests to a large extent on the capabilities of the HEIs to sense opportunities for accessing and seizing new resources, and then reconfiguring them internally. Berseck and Zu Knyphausen-Aufseß (2018) and Muneeb et al (2020), suggested that higher education policymakers need capabilities to use and recombine resources efficiently while simultaneously adapting to their changing environments for HEI competitiveness. It can be argued that DCs are instrumental in determining the capacity of a firm to successfully implement actions that result in a sustained competitive advantage (Hou and Chien, 2010).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dicho potencial deberá ser superior al de las demás IES si se desea garantizar el sostenimiento de la ventaja competitiva. Más aún, la reputación implica una combinación compleja entre recursos, la interdependencia entre ellos y la gestión efectiva de actividades en todas las áreas organizacionales de la IES (Muneeb et al, 2020).…”
Section: Estructura Capital Relacionalunclassified